Optical Mode Calculation in Large-Area Photonic Crystal Surface-Emitting Lasers - Mindaugas Radziunas; Eduard Kuhn; Hans Wenzel; Ben King; Paul Crump (IEEE Photonics Journal)
We discuss algorithms and numerical challenges in constructing and resolving spectral problems for photonic crystal surface-emitting lasers (PCSELs) with photonic crystal layers and large (up to several tens of mm $^{2}$ ) emission areas. We show that finite difference schemes created using coarse numerical meshes provide sufficient accuracy for several major (lowest-threshold) modes of particular device designs. Our technique is applied to the example of large-area all-semiconductor PCSELs, showing how it can be used to optimize device performance.